Sulfur Metabolisms in Epsilon- and Gamma-Proteobacteria in Deep-Sea Hydrothermal Fields - Yamamoto, Masahiro; Takai, Ken (Frontiers in Microbiology, 2011)
In deep-sea hydrothermal systems, super hot and reduced vent fluids from the subseafloor blend with cold and oxidized seawater. Very unique and dense ecosystems are formed within these environments. Many molecular ecological studies showed that chemoautotrophic epsilon- and gamma-Proteobacteria are predominant primary producers in both free-living and symbiotic microbial communities in global deep-sea hydrothermal fields. Inorganic sulfur compounds are important substrates for the energy conservative metabolic pathways in these microorganisms. Recent genomic and metagenomic analyses and biochemical studies have contributed to the understanding of potential sulfur metabolic pathways for these chemoautotrophs. Epsilon-Proteobacteria use sulfur compounds for both electron-donors and -acceptors. On the other hand, gamma-Proteobacteria utilize two different sulfur-oxidizing pathways. It is hypothesized that differences between the metabolic pathways used by these two predominant proteobacterial phyla are associated with different ecophysiological strategies; extending the energetically feasible habitats with versatile energy metabolisms in the epsilon-Proteobacteria and optimizing energy production rate and yield for relatively narrow habitable zones in the gamma-Proteobacteria.